Increased Adipose Tissue Expression of Interferon Regulatory Factor (IRF)-5 in Obesity: Association with Metabolic Inflammation - Sardar Sindhu; Reeby Thomas; Shihab Kochumon; Ajit Wilson; Mohamed Abu-Farha; Abdullah Bennakhi; Fahd Al-Mulla; Rasheed Ahmad (Cells, 2019)
Interferon regulatory factor (IRF)-5 is known to be involved in M1 macrophage polarization, however, changes in the adipose expression of IRF5 in obesity and their relationship with the local expression of proinflammatory cytokines/chemokines are unknown. Therefore, IRF5 gene expression was determined in the subcutaneous adipose tissue samples from 53 non-diabetic individuals (6 lean, 18 overweight, and 29 obese), using real-time RT-PCR. IRF5 protein expression was also assessed using immunohistochemistry and/or confocal microscopy. Adipose gene expression of signature immune metabolic markers was also determined and compared with adipose IRF5 gene expression. Systemic levels of C-reactive protein and adiponectin were measured by ELISA. The data show that adipose IRF5 gene (P = 0.008) and protein (P = 0.004) expression was upregulated in obese compared with lean individuals. IRF5 expression changes correlated positively with body mass index (BMI; r = 0.37/P = 0.008) and body fat percentage (r = 0.51/P = 0.0004). In obese, IRF5 changes associated positively with HbA1c (r = 0.41/P = 0.02). A good agreement was found between gene and protein expression of IRF5 in obese subjects (r = 0.65/P = 0.001). IRF5 gene expression associated positively with adipose inflammatory signatures including local expression of TNF-α, IL-6, CXCL8, CCL-2/5, IL-1β, IL-18, CXCL-9/10, CCL7, CCR-1/2/5, TLR-2/7/8/9, IRF3, MyD88, IRAK-1, and inflammatory macrophage markers (P < 0.05). Interestingly, IRF5 gene expression correlated positively with CRP (r = 0.37, P = 0.03) and negatively with adiponectin levels (r = −0.43, P = 0.009). In conclusion, elevated adipose IRF5 expression in obesity concurs with the typical inflammatory signatures, locally and systemically. Hence, the IRF5 upregulation may represent a novel adipose tissue marker for metabolic inflammation.